The effect of lean supply chain strategy, agile supply chain strategy, and supply chain responsiveness on sustainable firm performance of manufacturing industries in Malaysia - Istimaroh, Istimaroh (2023)
Presently, the issues of production disruption, supply disruption, and major environmental that all caused unsustainable performance in the manufacturing sector. Moreover, carbon dioxide (CO2) emission has increased rapidly over the past few decades resulting in harmful outcomes such as global warming, climate change, water, and air pollution, and degrading environmental performance. Hence, the lack of empirical studies providing insights into how supply chain strategies and supply chain responsiveness can provide sustainable performance for further research. This study aimed to analyze the supply chain responsiveness mediating effect on lean supply chain strategy, agile supply chain strategy, and sustainable performance relationships. The data collection instrument used was a questionnaire administered to a total sample of 231 manufacturers in Malaysia. The response rate was 66% while 51% were usable questionnaires. Sample selection was based on a purposive sampling technique. Smart- PLS analyses revealed that three dimensions of supply chain responsiveness, namely operating system, logistics process, and supplier network have impacted the practices between lean supply chain strategy, agile supply chain strategy, and sustainable performance relationships with partial mediation. Supply chain responsiveness mediated the relationship between the lean supply chain strategy and sustainable firm performance. Supply chain responsiveness also mediated the relationship between agile supply chain strategy and sustainable firm performance. Furthermore, both of them have a partially positive and significant influence on the relationships between lean supply chain strategy, agile supply chain strategy, and, sustainable firm performance. The study contributes firstly, to the body of knowledge by examining the mediating roles of supply chain responsiveness. Secondly, it complements the resource-based view (RBV) theory regarding the interrelationships between firm resources, routines, capabilities, and performance. Thirdly, practitioners benefit from being aware of the Strategies outlined in this study for overcoming expected business issues. Lastly, the study confirms the idea that every practice and capability established within the firm will eventually affect a certain area of performance